Orientações sobre vacinação contra o HPV em escolas públicas no interior do Estado de São Paulo - Conceição, Caio Vinicius (2021)
The aim of this research is to promote educational health actions to make students from public schools conscious about vaccination against the human papillomavirus, in a city in the state of São Paulo. This analysis was developed in the form of experience report, which was used audiovisual resources. It came out lack of knowledge from the students about the subject and the purpose of the vaccine. It is suggested that other educational actions will be taken to provide guidance in new vaccination campaigns.